2018
DOI: 10.1002/jcb.27256
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cε targets respiratory chain and mitochondrial membrane potential but not F0F1‐ATPase in renal cells injured by oxidant

Abstract: We have previously shown that protein kinase Cε (PKCε) is involved in mitochondrial dysfunction in renal proximal tubular cells (RPTC). This study examined mitochondrial targets of active PKCε in RPTC injured by the model oxidant tert-butyl hydroperoxide (TBHP). TBHP exposure augmented the levels of phosphorylated (active) PKCε in mitochondria, which suggested translocation of PKCε to mitochondria after oxidant exposure. Oxidant injury decreased state 3 respiration, adenosine triphosphate (ATP) production, ATP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 54 publications
(213 reference statements)
0
4
0
Order By: Relevance
“…Infusion of NaHS reduced heart rate and body temperature, indicative of a hypo–metabolic state. NaHS infusion also reduced sepsis–related lung and kidney injury, increased expression of α–tubulin and protein kinase C-ϵ, which act as regulators of respiration ( Rostovtseva et al., 2008 ; Nowak and Bakajsova-Takacsova, 2018 ), and help to prevent mitochondrial membrane damage during sepsis ( Aslami et al., 2013 ).…”
Section: The Role Of Host-derived H 2 S In Microbimentioning
confidence: 99%
“…Infusion of NaHS reduced heart rate and body temperature, indicative of a hypo–metabolic state. NaHS infusion also reduced sepsis–related lung and kidney injury, increased expression of α–tubulin and protein kinase C-ϵ, which act as regulators of respiration ( Rostovtseva et al., 2008 ; Nowak and Bakajsova-Takacsova, 2018 ), and help to prevent mitochondrial membrane damage during sepsis ( Aslami et al., 2013 ).…”
Section: The Role Of Host-derived H 2 S In Microbimentioning
confidence: 99%
“…PKCε also phosphorylates VDAC resulting in VDAC opening in cardiac cells . We have shown that the activation of PKCε in the renal proximal tubular cells exacerbates the dysfunction of mitochondrial complexes I and III and oxidant production after hypoxia and oxidant‐induced injury . Further, our studies in vivo in mice demonstrated that the deletion of PKCε protects the kidney against morphological damage and decreases in renal functions after ischemia‐induced AKI .…”
Section: Introductionmentioning
confidence: 62%
“…It has been shown that mitochondrial dysfunction is involved in the pathogenesis of AKI and triggers the progression from AKI towards CKD 10–13 . Proximal renal tubular dysfunction caused by AKI reduced the activity of mitochondrial complex I and the production of adenosine triphosphate (ATP) 14 . In accordance, restoring the function and homeostasis of mitochondria is a feasible strategy to prevent AKI 15 .…”
Section: Introductionmentioning
confidence: 99%
“… 10 , 11 , 12 , 13 Proximal renal tubular dysfunction caused by AKI reduced the activity of mitochondrial complex I and the production of adenosine triphosphate (ATP). 14 In accordance, restoring the function and homeostasis of mitochondria is a feasible strategy to prevent AKI. 15 Therefore, the control of mitochondrial dynamics is likely a useful strategy for dealing with kidney dysfunction induced by ischemia and hypoxia.…”
Section: Introductionmentioning
confidence: 99%